THE AROMATIC PROFILE OF WHITE WINES OBTAINED FROM BIODYNAMIC AND CONVENTIONAL GROWN GRAPES IN ROMANIA - Ana Maria TOADER; Cintia Lucia COLIBABA; Camelia Elena LUCHIAN; Andreea POPÎRDĂ; Bogdan NECHITA; Valeriu V. COTEA (Journal of Applied Life Sciences and Environment)
This study analyses the differences between wines obtained from grapes cultivated conventionally and those cultivated biodynamically. The wine samples studied were obtained from Rhein Riesling, Italian Riesling, Muscat Ottonel and Chardonnay grape varieties. Among these, four variants (one from each grape variety) were obtained from grapes following conventional cultural technologies, while the rest were from the same grape varieties cultivated biodynamically. All grapes and wines were produced in the Murfatlar vineyard, in south-east Romania. Basic chemical and sensorial analyses were applied to evaluate the differences appearing between the conventional and organic wine samples. All sets of data, PCA analysed, underlined that there are no systematic differences between the two grape cultivation methods and the obtained products.